2014
DOI: 10.1007/s40620-014-0145-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of allograft nephrectomy following kidney graft failure: preliminary experience with pre-operative angiographic kidney embolization

Abstract: Delayed graft function and early GF are associated with a higher rate of AN. PAKE may result in less blood loss, fewer transfusions, reduced operating time, and shorter length of stay, which may translate into reductions in morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(70 reference statements)
0
2
1
Order By: Relevance
“…The same finding was reproduced by Al‐Geizawi et al . . In our study, although it was reported in four of five patients (80%), wound site‐related infection was the only complication after subsequent surgical removal, of which the evolution was generally favourable with drainage and local care.…”
Section: Discussioncontrasting
confidence: 46%
“…The same finding was reproduced by Al‐Geizawi et al . . In our study, although it was reported in four of five patients (80%), wound site‐related infection was the only complication after subsequent surgical removal, of which the evolution was generally favourable with drainage and local care.…”
Section: Discussioncontrasting
confidence: 46%
“…However, the risk on necrotic pyelonephritis and post-embolization syndrome are increased after RAE and RAE as monotherapy is not widely used (200). However, using RAE as neo-adjuvant intervention before GN was shown to reduce both blood loss and operating time (201)(202)(203).…”
Section: Alternativesmentioning
confidence: 99%
“…These graft-related complications can be avoided by using RAE as a “neo-adjuvant” intervention, one or two days before GN. This combined approach appears to reduce the intraoperative blood loss [ 24 26 ] and operative time of GN [ 24 , 26 ]. Less common complications of RAE include arterial pseudoaneurysm [ 27 ] and coil migration with limb embolisation [ 28 ].…”
Section: Non-surgical Devascularisationmentioning
confidence: 99%